(untitled) (Marketing Journal, 2025)
This article analyzes the role and significance of social networks in the international tourism market. The study explores the growing influence of social media in tourism marketing in the post -COVID -19 era, the modern structure of the international touris m market, and its geographical distribution. Based on data from the United Nations World Tourism Organization (UNWTO), the article examines the size of the global tourism market, its role in the world economy, and its key players. Additionally, the regiona l distribution of the tourism market and the unique characteristics of each region are discussed. 203